Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.2 - The Product and Quotient Rules - 3.2 Exercises - Page 188: 19



Work Step by Step

$y=\dfrac{s-\sqrt{s}}{s^{2}}$ Rewrite the function like this: $y=s^{-2}(s-s^{1/2})=s^{-1}-s^{-3/2}$ Differentiate each term: $y'=-s^{-2}-(-\dfrac{3}{2})s^{-5/2}=-s^{-2}+\dfrac{3}{2}s^{-5/2}=-\dfrac{1}{s^{2}}+\dfrac{3}{2s^{5/2}}=-\dfrac{1}{s^{2}}+\dfrac{3}{2\sqrt{s^{5}}}$ Please note that there was an easier way to differentiate the function than using the quotient rule
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.